Gibberellin delays metabolic shift during tomato ripening by inducing auxin signaling - Park, Me-Hea; Malka, Siva Kumar (Frontiers in Plant Science, 2022)
Fruit ripening involves the dynamic interaction of phytohormones. Ethylene (ET) and gibberellin (GA) antagonistically affect fruit ripening. However, the mechanism of GA and its potential interaction with ET during fruit ripening remain unknown. To identify the potential molecular mechanism of ET and GA interplay in tomato (Solanum lycopersicum L.) fruit ripening, transcriptome and metabolomic profiling was carried out in tomato fruit treated with GA, ET or the combination of the two hormones (GA+ET). ET accelerated fruit ripening with the simultaneous repression of auxin signaling. In contrast, gibberellin delayed ripening by the upregulation of auxin signaling. ET signaling and response was inhibited by GA or combined with ET. At the metabolite level, while GA treatment inhibited metabolite shift during ripening, ET treatment promoted. In the combined hormone treatment, ET reduced or recovered GA inhibitory effect on specific metabolites. This study provided insight into ET and GA interaction, highlighting the importance of auxin signaling in metabolic shifts during tomato ripening progression.